Non-aqueous electrolyte and battery

By using a nonaqueous electrolyte containing fluorine and bromine substituents in the secondary battery, the problem of destruction of the positive electrode material at high voltage is solved, and the stable operation and cycling performance of the battery is improved at high voltage.

CN119481265APending Publication Date: 2025-02-18SHENZHEN HIGHPOWER TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411438187.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing secondary batteries are prone to damage to the positive electrode material at high voltages, resulting in transition metal dissolution and battery capacity attenuation.

Method used

A nonaqueous electrolyte solution is used, which comprises an electrolyte salt, an organic solvent and a first additive. The fluorine substituent and bromine substituents in the first additive work together to form a LiF-rich SEI film and LiBr, inhibit the dissolution of the transition metal and protect the positive electrode material.

Benefits of technology

In a high voltage environment, effectively suppress the dissolution of transition metals, protect the positive electrode material, improve the cycle performance and safety performance of the battery, and extend the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481265A_ABST
    Figure CN119481265A_ABST
Patent Text Reader

Abstract

In order to solve the problem that a positive electrode material of an existing battery is easy to damage under high voltage, the invention provides a non-aqueous electrolyte and a battery, the non-aqueous electrolyte comprises an electrolyte salt, an organic solvent and a first additive, and the first additive comprises one or more of compounds shown in formulas 1-3 and # imgabs0 #, each of R1-R6, R7-R12 and R13-R17 contains at least one fluorine substituent group and at least one bromine substituent group; the rest substituent groups are respectively and independently selected from halogen substituted or unsubstituted C1-C20 alkyl, halogen substituted or unsubstituted C1-C20 alkoxy, halogen substituted or unsubstituted C1-C20 aryl, halogen substituted or unsubstituted C1-C20 aryloxy, hydrogen, hydroxyl, carboxyl, phosphate, metal salt of phosphate, phosphite, metal salt of phosphite and pyrophosphate, and the rest substituent groups are independently selected from halogen substituted or unsubstituted C1-C20 alkyl, halogen substituted or unsubstituted C1-C20 alkoxy, halogen substituted or unsubstituted C1-C20 aryl, halogen substituted or unsubstituted C1-C20 aryloxy, hydrogen, hydroxyl, carboxyl, phosphate, metal salt of phosphate and pyrophosphate. A metal salt of a pyrophosphate ester, a sulfate ester, a metal salt of a sulfate ester, a sulfonic acid group, a metal salt of a sulfonic acid, a sulfinic acid group or a metal salt of a sulfinic acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a non-aqueous electrolyte and a battery. Background Art

[0002] Secondary batteries have been increasingly widely used in household appliances, portable electronic devices, and electric vehicles due to their high energy density and high voltage. In recent years, with the continuous development of secondary battery technology, high operating voltage, high temperature cycle and high temperature storage performance have become important performance indicators of secondary batteries. At present, when the high voltage is above 4.4V, the commonly used positive electrode materials such as lithium cobalt oxide and ternary materials will react with the electrolyte during the cycle, resulting in a decrease in battery performance, especially ternary materials. The Ni-O on its surface is easily attacked by the acidic components of the electrolyte, and Ni 4+ It will oxidize the electrolyte components and cause the battery to produce gas, causing the battery to swell, causing damage to the positive and negative electrode materials, leading to the dissolution of a large amount of transition metals, causing the battery capacity to decay, and further affecting the battery's cycle performance. Therefore, how to make secondary batteries operate stably at high voltage is the focus of battery research. Summary of the invention

[0003] Aiming at the problem that the positive electrode material of the existing secondary battery is easily damaged under high voltage, the present invention provides a non-aqueous electrolyte and a battery.

[0004] The technical solution adopted by the present invention to solve the above technical problems is as follows: In one aspect, the present invention provides a non-aqueous electrolyte solution, comprising an electrolyte salt, an organic solvent and a first additive, wherein the first additive comprises one or more compounds represented by Formulae 1 to 3. Wherein, each of R1-R6, R7-R12, and R13-R17 contains at least one fluorine substituent and at least one bromine substituent; the remaining substituents in R1-R17 are independently selected from halogen-substituted or unsubstituted C1-C20 hydrocarbon groups, halogen-substituted or unsubstituted C1-C20 alkoxy groups, halogen-substituted or unsubstituted C1-C20 aryl groups, halogen-substituted or unsubstituted C1-C20 aryloxy groups, hydrogen, hydroxyl, carboxyl, phosphate, metal salt of phosphate, phosphite, metal salt of phosphite, pyrophosphate, metal salt of pyrophosphate, sulfate, metal salt of sulfate, sulfonic acid, metal salt of sulfonic acid, sulfinic acid or metal salt of sulfinic acid.

[0005] Optionally, the mass content of the first additive in the non-aqueous electrolyte is 0.01%~5%.

[0006] Optionally, the mass content of the first additive in the non-aqueous electrolyte is 1.5%~3%.

[0007] Optionally, the first additive includes one or more of formulas A to K, .

[0008] Optionally, the electrolyte salt includes at least one of a lithium salt, a sodium salt, a potassium salt, a magnesium salt, a zinc salt and an aluminum salt; And / or, the concentration of the electrolyte salt is 0.5M~2.0M.

[0009] Optionally, the electrolyte salt includes MClO4, MBF4, MPF6, MAsF6, MPF2O2, MCF3SO3, MTDI, MB(C2O4)2, MBF2C2O4, M[(CF3SO2)2N], M[(FSO2)2N] and M[(C m F 2m+1 SO2)(C n F 2n+1 SO2)N], wherein M is Li, Na or K, and m and n are natural numbers.

[0010] Optionally, the organic solvent includes one or more of carbonate solvents, ether solvents, and carboxylate solvents.

[0011] Optionally, the non-aqueous electrolyte further includes a second additive, which includes one or more of fluoroethylene carbonate, biphenyl, fluorobenzene, vinylene carbonate, trifluoromethylethylene carbonate, vinylethylene carbonate, 1,3-propane sultone, 1,4-butane sultone, vinyl sulfate, vinyl sulfite, succinonitrile, adiponitrile, 1,2-bis(2-cyanoethoxy)ethane and 1,3,6-hexanetrinitrile; The mass content of the second additive in the non-aqueous electrolyte is 0.1% to 10%.

[0012] In another aspect, the present invention provides a battery comprising a positive electrode sheet, a negative electrode sheet, a separator and the non-aqueous electrolyte as described in any one of the above.

[0013] Optionally, the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer, and the mass percentage of the total content of Al element in the positive electrode active material layer is 500-15000 ppm; The positive electrode active material layer includes one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium iron manganese phosphate, and lithium manganese oxide; And / or, the negative electrode sheet includes a negative electrode active material layer, and the negative electrode active material layer includes natural graphite, artificial graphite, mesophase micro carbon beads, hard carbon, soft carbon, silicon, silicon oxide, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, TiO2-Li4Ti5O 12 and one or more of Li-Al alloys.

[0014] In the present invention, the fluorine substituent in the first additive participates in the construction of the SEI on the negative electrode surface, and a LiF-rich SEI film can be formed in the presence of lithium salts. At the same time, during the operation of the battery, the C-Br bond at the bromine substituent breaks to generate LiBr and participates in the construction of the positive electrode CEI. Due to the synergistic effect between F and Br, the non-aqueous electrolyte inhibits the dissolution of transition metals under high voltage conditions, protects the positive electrode material from being destroyed, thereby stabilizing the surface structure of the positive and negative electrodes, and further improving the normal temperature and high temperature cycle performance of the battery. At the same time, the substituent of the phosphate group in the first additive can capture hydroxyl groups and hydrogen protons, thereby improving the flame retardant properties of the non-aqueous electrolyte. DETAILED DESCRIPTION

[0015] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0016] An embodiment of the present invention provides a non-aqueous electrolyte, including an electrolyte salt, an organic solvent and a first additive, wherein the first additive includes one or more compounds represented by Formulas 1 to 3. Wherein, each of R1-R6, R7-R12, and R13-R17 contains at least one fluorine substituent and at least one bromine substituent; the remaining substituents in R1-R17 are independently selected from halogen-substituted or unsubstituted C1-C20 hydrocarbon groups, halogen-substituted or unsubstituted C1-C20 alkoxy groups, halogen-substituted or unsubstituted C1-C20 aryl groups, halogen-substituted or unsubstituted C1-C20 aryloxy groups, hydrogen, hydroxyl, carboxyl, phosphate, metal salt of phosphate, phosphite, metal salt of phosphite, pyrophosphate, metal salt of pyrophosphate, sulfate, metal salt of sulfate, sulfonic acid, metal salt of sulfonic acid, sulfinic acid or metal salt of sulfinic acid.

[0017] In the present invention, the fluorine substituent in the first additive participates in the construction of the SEI on the negative electrode surface, and a LiF-rich SEI film can be formed in the presence of lithium salts. At the same time, during the operation of the battery, the C-Br bond at the bromine substituent breaks to generate LiBr and participates in the construction of the positive electrode CEI. Due to the synergistic effect between F and Br, the non-aqueous electrolyte inhibits the dissolution of transition metals under high voltage conditions, protects the positive electrode material from being destroyed, thereby stabilizing the surface structure of the positive and negative electrodes, and further improving the normal temperature and high temperature cycle performance of the battery. At the same time, the substituent of the phosphate group in the first additive can capture hydroxyl groups and hydrogen protons, thereby improving the flame retardant properties of the non-aqueous electrolyte. In some embodiments, the mass content of the first additive in the non-aqueous electrolyte is 0.01% to 5%. The electrolyte containing the first additive within the above content range can improve the high temperature and high pressure performance and safety performance of the battery cell and increase the cycle life of the battery.

[0018] In a specific embodiment, the mass content of the substance of structural formula I includes but is not limited to 0.01%, 0.05%, 0.08%, 0.1%, 0.13%, 0.16%, 0.19%, 0.22%, 0.25%, 0.28%, 0.31%, 0.34%, 0.37%, 0.4%, 0.43%, 0.47, 0.5%, 0.8%, 1.1%, 1.4%, 1.7%, 2%, 2.3%, 2.6%, 2.9%, 3.2%, 3.5%, 3.8%, 4.1%, 4.4%, 4.7% or 5%.

[0019] In a preferred embodiment, the mass content of the first additive in the non-aqueous electrolyte is 1.5% to 3%. The non-aqueous electrolyte containing the first additive that meets the above content range can further improve the high temperature and high pressure performance and safety performance of the battery and increase the cycle life of the battery.

[0020] In some embodiments, the first additive comprises one or more of formulas A to K, .

[0021] By selecting the above-mentioned additives, the high temperature and high pressure performance and safety performance of the battery cell can be further improved, and the flame retardant performance of the electrolyte can be improved.

[0022] In some embodiments, the electrolyte salt includes at least one of a lithium salt, a sodium salt, a potassium salt, a magnesium salt, a zinc salt, and an aluminum salt.

[0023] In some embodiments, the concentration of the electrolyte salt is 0.5 M to 2.0 M. The concentration of the electrolyte salt in the electrolyte is not particularly limited, but when the content of the electrolyte salt is lower than 0.5 M, the number of mobile electrolyte cations in the electrolyte is insufficient, and when the content of the electrolyte salt is higher than 2 M, the viscosity of the electrolyte may increase, resulting in an increase in the impedance of the electrolyte, which reduces the migration rate of the electrolyte cations and may reduce the performance of the battery.

[0024] In some embodiments, the electrolyte salt includes MClO4, MBF4, MPF6, MAsF6, MPF2O2, MCF3SO3, MTDI, MB(C2O4)2, MBF2C2O4, M[(CF3SO2)2N], M[(FSO2)2N], and M[(C m F 2m+1 SO2)(C n F 2n+1 SO2)N], wherein M is Li, Na or K, and m and n are natural numbers. By selecting the above-mentioned ionizable electrolyte salt, the number of electrolyte cations that can migrate in the electrolyte is guaranteed.

[0025] In a preferred embodiment, the electrolyte salt is selected from lithium salts, and the lithium salt is selected from one or more of organic electrolyte salts and inorganic electrolyte salts. Lithium salts include but are not limited to LiPF6, LiBF4, LiSbF6, LiAsF6, LiTaF6, LiAlCl4, Li2B 10 Cl 10 、Li2B 10 F 10 , LiClO4, LiCF3SO3, lithium bis(oxalatoborate) [LiB(C2O4)2], lithium bis(malonate)borate [LiB(O2CCH2CO2)2], lithium bis(difluoromalonate)borate [LiB(O2CCF2CO2)2], lithium malonate oxalateborate [LiB(C2O4)(O2CCH2CO2)], lithium difluoromalonate oxalateborate [LiB(C2O4)(O2CCF2CO2)], lithium tri(oxalatophosphate) [LiP(C2O4)3] and lithium tri(difluoromalonate)phosphate [LiP(O2CCF2CO2)3], trifluorosulfonyl lithium, difluoro(trifluoromethylsulfonyl)imide lithium, bis(fluorosulfonyl)imide lithium, tri(trifluoromethylsulfonyl)methyl lithium or one or more thereof.

[0026] The concentration of the lithium salt is preferably 0.9M to 1.3M.

[0027] In some embodiments, the organic solvent includes one or more of a carbonate solvent, an ether solvent, and a carboxylate solvent. Specifically, the carbonate solvent includes one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), fluoroethyl methyl carbonate (FEMC), fluorodimethyl carbonate (FDMC), and fluoropropylene carbonate (FPC).

[0028] The ether solvent includes one or more of 2-dimethoxyethane, ethylene glycol dimethyl ether, dimethoxydimethyl ether, diethylene glycol dimethyl ether, 1,3-dioxolane, triethylene glycol monoethyl ether, tetrahydrofuran, 2-methyl-tetrahydrofuran, 1,1,2,2-tetrafluoroethyl-2,2,2,3-tetrafluoropropyl ether, bis(2,2,2-trifluoroethyl) ether, 1,1,2,2,-tetrafluoroethyl-2,2,2-trifluoroethyl ether, methoxy nonafluorobutane, and ethoxy nonafluorobutane.

[0029] The carboxylic acid ester solvent includes one or more of ethyl propionate (EP), propyl propionate (PP), methyl propionate (MP), ethyl acetate (EA), and ethyl fluoroacetate (DFEA).

[0030] Taking the mass of the non-aqueous electrolyte as 100%, the content of the organic solvent is 70% to 90%. The viscosity of the electrolyte is improved by adjusting the content of the organic solvent to ensure the migration rate of lithium ions in the electrolyte.

[0031] In a specific embodiment, the content of the organic solvent is 70%, 75%, 80%, 85% or 90%.

[0032] In some embodiments, the non-aqueous electrolyte further includes a second additive, which includes one or more of fluoroethylene carbonate (FEC), biphenyl, fluorobenzene, vinylene carbonate, trifluoromethylethylene carbonate, vinyl ethylene carbonate, 1,3-propane sultone, 1,4-butane sultone, vinyl sulfate, vinyl sulfite, succinonitrile, adiponitrile, 1,2-bis(2-cyanoethoxy)ethane, and 1,3,6-hexanetrinitrile. By adding the second additive, a stable SEI is formed at the negative electrode, the negative electrode is further protected, the cycle performance of the battery at high voltage is improved, and the energy density of the battery is increased.

[0033] In some embodiments, the mass content of the second additive in the non-aqueous electrolyte is 0.1% to 10%. By regulating the content of the second additive, the occurrence of side reactions of the electrolyte during the charge and discharge process can be suppressed, the positive and negative electrodes can be better protected, the cycle performance of the battery under high voltage can be improved, and the energy density of the battery can be increased.

[0034] On the other hand, an embodiment of the present invention provides a battery, including a positive electrode sheet, a negative electrode sheet, a separator and a non-aqueous electrolyte as described in any one of the above embodiments. By selecting the non-aqueous electrolyte described in the above embodiment, the positive and negative electrodes of the battery working at a high voltage are protected, and side reactions between the positive electrode and the wastewater electrolyte are avoided, thereby improving the cycle life and energy density of the battery.

[0035] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer, and the mass percentage of the total content of Al element in the positive electrode active material layer is 500-15000 ppm.

[0036] In some embodiments, the positive electrode active material layer includes one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium iron manganese phosphate, and lithium manganese oxide.

[0037] The negative electrode sheet includes a negative electrode active material layer, and the negative electrode active material layer includes natural graphite, artificial graphite, mesophase micro carbon balls, hard carbon, soft carbon, silicon, silicon oxide, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, TiO2-Li4Ti5O 12 and one or more of Li-Al alloys.

[0038] The present invention is further described below by way of examples.

[0039] Example 1 This embodiment is used to illustrate the non-aqueous electrolyte and battery disclosed in the present invention, and includes the following operating steps: Preparation of non-aqueous electrolyte EC, DEC, and PC were mixed at a mass ratio of 1:1:1 to serve as an organic solvent. 1% of the first additive represented by formula A was added to the organic solvent, and after mixing evenly, LiPF6 was added to obtain an electrolyte having a LiPF6 concentration of 1.1 mol / L.

[0040] Production of positive electrode: The positive electrode active material lithium cobalt oxide, conductive agent CNT, and adhesive PVDF are fully stirred and mixed in NMP solvent at a weight ratio of 97:1.5:1.5, and the slurry is coated on aluminum foil. After drying, cold pressing, stripping, sheeting, welding of pole ears, and gluing, a positive electrode sheet that meets the requirements is made. Other positive electrode materials such as lithium manganese oxide (LiMn2O4), 532 ternary (LiNi 0.5 Co 0.3 Mn 0.2 ) were prepared in a similar manner.

[0041] Negative electrode production: The negative electrode active material graphite, conductive agent SP, thickener CMC, and adhesive SBR are mixed in a proper amount of deionized water solvent at a mass ratio of 96.3:1:1.2:1.5 to form a uniform negative electrode slurry. The slurry is applied to the negative electrode current collector copper foil, and then dried, cold pressed, stripped, sheeted, welded to the pole ear, and glued to form a negative electrode sheet that meets the requirements. Other negative electrode materials such as lithium titanate are prepared in a similar way.

[0042] Lithium-ion battery production: The positive electrode sheet, separator and negative electrode sheet are wound / stacked to obtain a bare cell. The bare cell is placed in the aluminum-plastic film that has been punched out to complete the top and side sealing. After high-temperature baking, liquid injection, static, formation, capacity division, testing and other processes, the battery is completed.

[0043] Example 2-13 The examples are used to illustrate the non-aqueous electrolyte and battery disclosed in the present invention, and include most of the operating steps in Example 1, except that the formulation in Table 1 is used.

[0044] Comparative Examples 1-4 The comparative example is used to compare and illustrate the non-aqueous electrolyte and battery disclosed in the present invention, and includes most of the operating steps in Example 1, except that the formula in Table 1 is used.

[0045] Table 1 Performance Testing 1. The lithium-ion batteries prepared in the above examples and comparative examples were subjected to the following performance tests: Test 1: Charge to 4.55V at 1C constant current and constant voltage at 25℃, cut-off current 0.05C, let stand for 10min, discharge to 3.0V at 1C, record discharge capacity C0 as initial capacity, repeat 200 cycles. The final capacity C of 200 cycles is 800 , then the capacity retention rate = C 200 / C0.

[0046] Test 2: Charge to 4.55V at 0.5C constant current and constant voltage at 45℃, cut-off current 0.05C, let stand for 10min, discharge to 3.0V at 0.5C, record discharge capacity C0 as initial capacity, repeat for 200 cycles. The final capacity C of 500 cycles is 200 , then the capacity retention rate = C 200 / C0.

[0047] The test results are shown in Table 2.

[0048] Table 2 It can be seen from the test results in Table 2 that the embodiment of the present invention can significantly improve the room temperature cycle performance and high temperature cycle performance of the lithium ion battery under high voltage by adding the non-aqueous electrolyte to the lithium ion battery.

[0049] From the test results of Examples 1 to 3 and Comparative Example 1, it can be seen that the first additives of different structures have different degrees of improvement on the room temperature cycle performance and high temperature cycle performance of lithium-ion batteries under high voltage, but are significantly better than Comparative Examples 1 to 4 without the first additive. In addition, the capacity of Comparative Example 1 decays to about 76% after about 100 cycles at 45°C and the cycle is terminated, while the embodiment can be cycled to 200 cycles and the capacity retention rate is still better than the capacity retention rate of Comparative Example 1 at the end. It can be seen that the first additive has a significant effect on improving the cycle stability of positive and negative electrode materials under high voltage. The introduction of the first additive can improve the high temperature and high pressure performance of lithium batteries and improve the safety of lithium batteries.

[0050] From the test results of Examples 1, 4 to 8, it can be seen that when the content of the first additive is in the range of 0.01% to 5%, the room temperature cycle performance and high temperature cycle performance of the lithium-ion battery under high voltage can be effectively improved. When the usage of the first additive is in the range of 1.5% to 3%, the cycle retention rate is optimal. From the test results of Examples 1, 10 to 12, it can be seen that the first additive and the second additive are used in combination to further improve the room temperature cycle performance and high temperature cycle performance of the lithium-ion battery under high voltage.

[0051] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A non-aqueous electrolyte, characterized in that: It includes an electrolyte salt, an organic solvent and a first additive, wherein the first additive includes one or more compounds represented by formulas 1 to 3, Wherein, each of R1-R6, R7-R12, and R13-R17 contains at least one fluorine substituent and at least one bromine substituent; the remaining substituents in R1-R17 are independently selected from halogen-substituted or unsubstituted C1-C20 hydrocarbon groups, halogen-substituted or unsubstituted C1-C20 alkoxy groups, halogen-substituted or unsubstituted C1-C20 aryl groups, halogen-substituted or unsubstituted C1-C20 aryloxy groups, hydrogen, nitro, cyano, hydroxyl, carboxyl, phosphate, metal salt of phosphate, phosphite, metal salt of phosphite, pyrophosphate, metal salt of pyrophosphate, sulfate, metal salt of sulfate, sulfonic acid, metal salt of sulfonic acid, sulfinic acid or metal salt of sulfinic acid.

2. The non-aqueous electrolyte according to claim 1, characterized in that The mass content of the first additive in the non-aqueous electrolyte is 0.01% to 5%.

3. The non-aqueous electrolyte according to claim 2, characterized in that The mass content of the first additive in the non-aqueous electrolyte is 1.5% to 3%.

4. The non-aqueous electrolyte according to claim 1, characterized in that The first additive comprises one or more of formulas A to K, 。 5. The non-aqueous electrolyte according to claim 1, characterized in that The electrolyte salt includes at least one of a lithium salt, a sodium salt, a potassium salt, a magnesium salt, a zinc salt and an aluminum salt; And / or, the concentration of the electrolyte salt is 0.5M~2.0M.

6. The non-aqueous electrolyte according to claim 5, characterized in that The electrolyte salts include MClO4, MBF4, MPF6, MAsF6, MPF2O2, MCF3SO3, MTDI, MB(C2O4)2, MBF2C2O4, M[(CF3SO2)2N], M[(FSO2)2N] and M[(C m F 2m+1 SO2)(C n F 2n+1 SO2)N], wherein M is Li, Na or K, and m and n are natural numbers.

7. The non-aqueous electrolyte according to claim 1, characterized in that The organic solvent includes one or more of carbonate solvents, ether solvents, and carboxylate solvents.

8. The non-aqueous electrolyte according to claim 1, characterized in that The non-aqueous electrolyte further includes a second additive, the second additive including one or more of fluoroethylene carbonate, biphenyl, fluorobenzene, vinylene carbonate, trifluoromethylethylene carbonate, vinylethylene carbonate, 1,3-propane sultone, 1,4-butane sultone, vinyl sulfate, vinyl sulfite, succinonitrile, adiponitrile, 1,2-bis(2-cyanoethoxy)ethane, and 1,3,6-hexanetrinitrile; The mass content of the second additive in the non-aqueous electrolyte is 0.1% to 10%.

9. A battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a separator and the non-aqueous electrolyte according to any one of claims 1 to 8.

10. The battery according to claim 9, characterized in that The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the total content of Al element in the positive electrode active material layer is 500-15000 ppm by weight; The positive electrode active material layer includes one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium iron manganese phosphate, and lithium manganese oxide; And / or, the negative electrode sheet includes a negative electrode active material layer, and the negative electrode active material layer includes natural graphite, artificial graphite, mesophase micro carbon beads, hard carbon, soft carbon, silicon, silicon oxide, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, TiO2-Li4Ti5O 12 and one or more of Li-Al alloys.

Citation Information

Patent Citations

  • Lithium ion battery electrolyte and secondary battery containing lithium ion battery electrolyte

    CN103715454A

  • Non-aqueous electrolyte and lithium-ion battery containing non-aqueous electrolyte

    CN110299561A

  • Secondary battery and preparation method and application thereof

    CN118693282A

  • Electrolytes for lithium transition metal phosphate batteries

    US20170207486A1